Understanding the lived experience of women before and after fistula repair: a qualitative study in Kenya. (19th February 2016) - Khisa, W; Wakasiaka, S; McGowan, L; Campbell, M; Lavender, T
Abstract : Objective: To gain understanding of the first‐hand experience of women prior to and following repair of a vaginal fistula, to determine the most effective support mechanisms. Design: Qualitative phenomenological study using a series of in‐depth semi‐structured interviews at two time points: prior to fistula repair and 6 months post‐surgery. Data were analysed thematically. Setting: Three fistula clinics in three districts in Kenya. Population: A purposive sample of 16 women suffering with vaginal fistula who were seeking fistula repair. Methods: Thrity‐two semi‐structured interviews were conducted. Results: The two main themes represented the women's journeys from social isolation to social reintegration . Women felt euphoric following fistula repair, believing that a 'miracle' had occurred. However, the 'post‐miracle phase' demonstrated that the social and psychological impact of fistula leaves scars that are not easily healed, even when fistula repair is successful. Conclusion: Women's experiences of living with fistula have an impact beyond that which can be repaired solely by surgery. The findings from this study support the need for more active psychological assessment in the management of women with fistula, and the role of targeted psychological support in any package of care given in the post repair phase. The format of this support requires further study. Engagement by health professionals with the wider community could raise awareness of the causes of fistula, and provide support for significant others who may also be feeling vulnerable. It is likely that the collaborative efforts from health professionals and community members will provide the most effective support. Tweetable abstract: Fistula surgery alone is insufficient for women's physical, social and psychological recovery. Tweetable abstract: Fistula surgery alone is insufficient for women's physical, social and psychological recovery.